(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2020)
As a results of the doctoral research Mascaramento Espacial: um processo criativo envolvendo a espacialidade corporal do ator, the article presents the stages of a creative process carried out at Escuela de Artes Dramáticas de la Universidade de Costa Rica (EAD-UCR), in which the bodily spatiality of the performer serves as a main matrix to construct their performance. The results point to methodological procedures based on the way the ambience bordering a path that comes from the dynamics and qualites of the movements, and subsequently affects both the creation of scenic actions and the organization these actions in physical scores.